The Telepolis as a Tool for Citizen Inclusion in Identity Construction - Choquehuanca, José Eduardo Villanueva (MAJ - Malaysia Architectural Journal, 2025)
Cities, as physical points on the space-time continuum, are defined by their diversity, the variations within this plane, and the responses to these variations. The unpredictable nature of urbanity in the contemporary era is being redefined by technology, altering the traditional sense of urban life. For the first time in history, it is no longer necessary to physically inhabit a city to participate in urban life. This has led to a greater range of variations across different realities, creating a multiplicity of socially distant realities with increasingly divergent interests that complicate social cohesion. This study aims to understand unpredictability and how identities and perceptions of the environment are formed and evolve around it. Through an interdisciplinary approach that combines scientific and psychological principles, it seeks to establish a framework for understanding and addressing these variations, using technology and Urban Proximity as facilitators to enhance social connections.